Empowerment of Women Farmers Group Jempiring, Bresela Village, Payangan District, Gianyar Regency, in Producing Traditional Snacks for "Celebrations" - Semariyani, A.A. Made; Saloko, Satrijo; Yasa, I Wayan Sweca; Suriati, Luh; Singapurwa, Ni Made Ayu Suardani; Sudiarta, I Wayan; Mangku, I Gede Pasek; Chindrawato, A.A. Sagung Manik; Setianingsih, Ni Luh Putu Putri; Laksmi, A.A. Ayu Kanaka Mutiara; Mulia, I Komang Oki Budi; Subin, Maria Reinaldis Jebaut; Putri, Ni Kadek Sintya Pradnyani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The group members of the Jempiring Women Farmers Group in Bresela Village have limited knowledge and skills in processing traditional snack products that are hygienic, varied, and suitable for sale for “upakara” (religious ritual) purposes. Most of the “upakara” snacks are purchased from outside the village, which has an impact on the community's low local income and lack of economic independence. The method of implementing the activity includes several stages, namely: socialization and counseling regarding the importance of sanitation and hygiene in food processing, practical training in making various types of traditional snacks, such as “jaja uli” and “jaja begina”, which are suitable for “upakara”, and assistance in terms of packaging, pricing, and product marketing. The results of this activity are very significant: the members of the Jempiring group are now not only able to produce traditional snacks independently but have also formed a local marketing network. This success not only increases the group's income but also preserves the traditional Balinese culinary heritage and strengthens the village's economic independence. Contribution to Sustainable Development Goals (SDGs):SDG 1 – No PovertySDG 5 – Gender EqualitySDG 8: Decent Work and Economic GrowthSDG 11 – Sustainable Cities and Communities